Management of a pediatric patient with rapidly progressive glomerulonephritis and cutaneous mucormycosis: a case report - Jia, Lili; Shi, Kaili; Sun, Xiaoyi; Xu, Feng; Sun, Tao; Gao, Chunlin (Frontiers in Pediatrics, 2025)
Mucormycosis is a highly invasive and rare opportunistic infection caused by mucor fungi, characterized by challenging diagnosis and rapid disease progression. It predominantly affects patients with compromised immune systems due to various reasons, such as kidney failure, long-term use of antibiotics or corticosteroids. We recently successfully treated a pediatric patient with rapidly progressive glomerulonephritis accompanied by severe cutaneous mucormycosis. To our knowledge, this is the first reported case of rapidly progressive glomerulonephritis nephritis accompanied by dermatophytosis in a pediatric patient. In this case, we share our management experience, including special nursing experience. Cutaneous mucormycosis progresses quickly and is difficult to diagnose and treat, especially in children with compromised immune function, warranting high vigilance from clinicians and nursing staff. Early diagnosis and targeted treatment are crucial for improving the prognosis of patients. Therefore, once there is a suspicion of a mucormycosis infection, we recommend the early application of various testing methods such as fungal culture, skin biopsy and genetic testing in order to to promptly confirm the diagnosis.